Complete blood count parameters as potential predictive factors of brain metastases in lung cancer - Marschollek, Karol; Kosacka, Monika; Pokryszko-Dragan, Anna; Brzecka-Bonnaud, Anna (Frontiers in Oncology, 2025)
IntroductionBrain metastases are common and devastating complication of the lung cancer (LC) but predictive biomarkers for their risk are still lacking.ObjectivesTo analyze the relationships between complete blood count (CBC)-based and selected biochemical indices and occurrence of brain metastases in patients diagnosed with LC.Patients and methodsThe study was based on retrospective analysis of medical records of 217 patients diagnosed with LC and undergoing follow-up in one specialist center. Clinical and laboratory data on admission were determined, including: neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), neutrophil-to-platelet ratio (NPR) and red cell distribution width-to-platelet ratio (RPR) and selected biochemical parameters. Relationships were evaluated between these parameters and occurrence of brain metastases, other distant metastases and death within 12 months of follow-up.Results168 patients had the follow-up data for 6 months, and 128 - for 12 months. Brain metastases were detected in 41 patients and 1-year mortality rate was 17.61%. Patients who developed brain metastases during 12 months had significantly higher baseline NLR (4.66 vs 2.75, p<0.001), PLR (170.83 vs 142.42, p=0.03) and lower LMR (1.61 vs 2.33, p=0.008).In univariate analysis, higher leukocyte count (HR 1.08, p=0.016), neutrophil count (HR 1.11, p=0.0036), NLR (HR 1.09, p=0.005), d-dimer levels (HR 1.0002, p=0.0043), and lower LMR (HR 0.67, p=0.018) were significantly associated with the risk of developing brain metastases. Liver metastases were associated with lower LMR (1.69 vs 2.29, p=0.04), while metastases to the other lung – with lower PLR (126.52 vs 161.8, p=0.02) and higher LMR (2.51 vs 1.96, p=0.02) and RPR (0.184 vs 0.154, p=0.03). No significant relationships were found between CBC-based indices and mortality.ConclusionsCBC-based indices could be useful and easily accessible predictive markers of brain metastases in the patients with lung cancer.